Unveiling the dual-edged roles of melanocytes: Key insights into skin photoaging and therapeutic avenues - Xiaorong Jia; Li He (Pharmacological Research, 2025)
The skin, the body's largest organ, serves as the primary barrier against external damage. Skin aging can act as a visible proxy and a triggering factor for systemic aging. External environmental stimuli, particularly inappropriate and prolonged ultraviolet (UV) exposure, drive skin photoaging, inducing structural and functional changes, including pigment abnormalities. Melanocytes, specialized cells that absorb light radiation, play a crucial role in protecting the skin from photoaging. In this article, we review the latest evidence emphasizing the dual role of melanocytes in photoaging, presenting diverse perspectives, and summarizing its regulatory mechanisms and dynamic changes during this process. Moreover, we discuss recent advances in therapeutic drug research targeting melanocyte-related pathways. Clarifying the roles of melanocytes during skin photoaging provides important insights that are essential for advancing dermatological treatments.